Diversity of tue bugs (hemiptera : Heteroptera) in mount Serambu, Bau, Sarawak - Zalwani, Bt Ahamad (Universiti Malaysia Sarawak, UNIMAS, 2013)
A study on heteropterans diversity was conducted in Mount Serambu, Bau, Sarawak from 19th January until 29th January 2013 and 4th February until 16th February 2013. The aims of this study were to investigate the diversity of the true bugs at Mount Serambu, Bau and to establish database of true bugs for future references. A total of 531 individuals from 49 species were captured by using Modified Pennsylvania light traps, beating and handpicking methods. Shannon (H’) indices showed that species diversity was highest at lower elevation (H’=2.441) compared to upper elevation (H’=1.651). The abundant of individuals was higher at lower elevation with a total of 441 individuals compared to upper elevation with only 90 individuals. The most abundant species captured was Leptocorisa sp. with relative abundance 27.9 % and followed by Leptocorisa acuta with 25.8%. The most diverse family recorded was Alydidae with 308 individuals (58%) and followed by Coreidae with 57 individuals (11%). In terms of number of species captured, the most abundant family assigned to Reduviidae with a total 16 species (32.7%).